ПОВ'ЯЗАНА З МЕРЕЖЕЮ ФОТОПЕРЕТВОРЮВАЛЬНА СИСТЕМА З ТРЬОМА ІНВЕРТОРАМИ, ЩО РЕГУЛЮЮТЬСЯ НА БАЗІ СХЕМИ СИНХРОННОЇ ШИМ - Олещук, В.І. (Інститут електродинаміки НАН України, Київ, 2022)
The paper presents comparative analysis of three versions of the modified scheme of space-vector-based synchronous pulsewidth modulation (PWM), applied for control of three two-level inverters of transformer-based photovoltaic (PV) system, and focused on providing of the symmetry of winding voltage of power transformer during the whole adjustment range. Power supply of inverters is providing by the corresponding three solar strings consisting of a set of PV panels, and the outputs of three inverters are connected specifically with inverter-side windings of multi-winding grid-tired transformer. Results of MATLAB-simulation prove the fact of advanced spectral composition of the winding voltage of triple-inverter-based PV installation regulated by algorithms of synchronous space-vector PWM, assuring potential reduction of losses in these systems. References 10, table 1, figures 9.